UNIONIZATION IN MEXICO DURING THE NEOLIBERAL PERIOD 1984-2006 - Zepeda Martínez, Roberto (2014)
This article analyzes the variations of union density in Mexico during the period 1984-2006. Union affiliation is examined by industry, occupation and region, as well as by sociodemographiccharacteristics of union members. A general assessment of unionizationlevels in recent decades is conducted, according to official data and academic publications.Statistical data, demonstrate a decline of unionization in total labor force between 1989and 1996.